Health-related quality of life among people living with HIV/AIDS receiving case management. Issue 2 (2nd April 2016) - Cesnales, Nicole I.; Thyer, Bruce; Albright, David; Neujahr, Nicholas
ABSTRACT: Using a cross-sectional descriptive survey, we assessed the health-related quality of life (HRQOL) of 97 people living with HIV/AIDS receiving case management services in the Big Bend area of northern Florida. There is only one AIDS service organization and only one Ryan White Program–supported HIV/AIDS medical care provider in the region. Improvement in HRQOL is a treatment goal set by the Ryan White Program and is a common goal of HIV case management. Results indicate mild symptom burden, mild functional impairment, and poor HRQOL. Implications for HIV case management and social work and practice are discussed.